Strategi Pengembangan The Ogoh-Ogoh Bali Collection Sebagai Atraksi Wisata Pendukung Di Kawasan Daya Tarik Wisata Pura Taman Ayun, Kabupaten Badung - Norastika, Saldana Devin Ayu; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i02.p10, 2019)
Gallery Ogoh – ogoh in Yadnya Museum is a collection of objects og various shapes ogoh – ogoh. The building gallery ogoh – ogoh is right beside the Taman Ayung, Mengwi. Gallery ogoh – ogoh is very usefull for tourists who did not get to see ogoh – ogoh during Nyepi day. So they are more enjoyable to see anytime the uniqueness of ogoh – ogoh itself. Application concept Museum is an essential componenr to be used as a benchmark to improve the quality and facilities at gallery ogoh – ogoh as a tourist attraction. This study aims to anlyze the applictions concept museum on gallery ogoh – ogoh for tourist attraction. Data was collected through observation, unstructured interviews, literature study and documentation.  Determinationtechniquesinformant/sampleispurposive . For the determination ofthe sampleusing “ sampleimplementationanalysis” , by taking theexample ofthe bestmuseumsinBalias a benchmarktobe used asan example ofa conceptthatwill beapplied to thegalleryogoh-ogohas a tourist attraction . The concept of the museum which was applied to the gallery ogoh- ogoh seen from the standard guidelines of founding a museum, so it can be explained from any related components. As a tourist attraction gallery ogoh - ogoh has had 1) Attractions (Attractions) is good, 2) Accessibility (accessibilities) is enough, 3) Amenities or facilities(suit) is enough, 4)Ancillaryservices namely tourism organizations required for tourist services ares till not good. The results of this study also provides recommendations to the manager  gallery ogoh- ogoh to improve facilities and quality as an attraction that can be presented to tourists. Keyword: Ogoh – ogoh, Concept Museum, Tourist Attraction